Pemberdayaan Perempuan Melalui Kelompok Mentari (Menuai Kreativitas Istri) dalam Meningkatkan Nilai Ekonomi Susu Kambing Ettawa Kecamatan Percut Sei Tuan - Batubara, Beby Masitho; Riadi, Selamat; Rahmiati, Rahmiati (Pelita Masyarakat, 2024)
The production of Ettawa goat milk from the Mentari women's group breeders is quite high but this is inversely proportional to the management of goat milk processing which should get a lot of economic value from the milk produced by the Mentari women's group. The production of Ettawa goat's milk, which has been running so far, has no economic value for goat breeders and is still processed conventionally. This problem is also strengthened by the members' knowledge of using technology so that there is no regular promotion or marketing either directly or using online media such as Instagram. , Facebook, E-Commerce, or website. Apart from that, so far the Ettawa goat's milk produced is only fresh milk, with production results which on certain days are quite high, not commensurate with consumer demand, which in the end the quality of the milk has been damaged, and cannot be resold, there is no milk processing, as variations in the use of milk and its economic value into various products such as yogurt and kefir (with fermentation), and soap. Milk processing is not carried out by the Mentari women's group because of limited knowledge, technology, and production equipment to process goat's milk. The importance of training and assistance on how to process Ettawa goat milk into various dairy products that have economic value and are liked by consumers, the use of technology for online marketing and sales as well as institutional strengthening of the Mentari women farmer group as a group that collaborates in milk processing and milk marketing and variants together to move towards a more professional group.